Gods, birds, and trees; Variation in illustrated Javanese pawukon manuscripts - Meij, Dick van der (Wacana, Journal of the Humanities of Indonesia, 2019)
Many libraries in the world own illustrated manuscripts containing calendrical divination based on the Javanese 30 seven-day wuku cycle. Although the contents of these pawukon manuscript have been studied, the illustrations they often contain have almost been ignored. Apart from stating that these illustrations usually depict the gods, trees, buildings, and birds associated with each individual wuku, the variety among these illustrations has escaped scholars so far. Variation is found at many levels such as the general lay-out of the illustrations, the depiction of the various gods, trees, et cetera but also with reference to the position of the illustrations and the accompanying texts that explain the characteristics and divination possibilities of each wuku. This article intends to offer a start into the study of these illustrations by offering examples of these illustrations and the connections that may have existed between the makers of these illustrated manuscripts.